ENVIRONMENTAL LITERACY IN ELEMENTARY EDUCATION THROUGH ECOTHEOLOGY-INTEGRATED MULTIMODAL LEARNING - Dewi Puspitasari; Nur Khasanah; ELY MUFIDAH; RAFILA KASAMIRA DEWI ABRORI; CHUSNA MAULIDA; AKHMAD AFRONI; GUNAWAN AJI; AULIA AMINI (Linguists : Journal of Linguistics and Language Teaching, 2026)
Environmental degradation presents an urgent challenge that requires early educational responses grounded not only in knowledge acquisition but also in ethical responsibility toward nature. This study explores how environmental literacy among elementary school students can be fostered through ecotheology-informed multimodal learning. Employing a mini participatory action research design, the study was conducted with fifth-grade students at an elementary school in Indonesia. Students engaged in a multimodal project centered on environmental issues, with drawing used as the primary medium for expressing understanding and reflection. Data were collected through students’ drawings, classroom observations, and oral explanations, and analyzed qualitatively. The findings indicate that multimodal learning supported students’ comprehension of environmental issues such as pollution, deforestation, and climate change while encouraging emotional engagement and a sense of responsibility toward nature. From an ecotheological perspective, students’ representations reflected values of care, stewardship, and moral accountability for the environment, positioning nature as something to be protected rather than exploited. This study demonstrates that ecotheology-informed multimodal learning can provide meaningful learning experiences for young learners and contribute to the development of environmental literacy in elementary education.